Myosin XI drives polarized growth by vesicle focusing and local enrichment of F-actin in Physcomitrium patens. Issue 4 (23rd September 2021) - Galotto, Giulia; Wisanpitayakorn, Pattipong; Bibeau, Jeffrey P; Liu, Yen-Chun; Furt, Fabienne; Pierce, Ellen C; Simpson, Parker J; Tüzel, Erkan; Vidali, Luis
Abstract: In tip-growing plant cells, growth results from myosin XI and F-actin-mediated deposition of cell wall polysaccharides contained in secretory vesicles. Previous evidence showed that myosin XI anticipates F-actin accumulation at the cell's tip, suggesting a mechanism where vesicle clustering via myosin XI increases F-actin polymerization. To evaluate this model, we used a conditional loss-of-function strategy by generating moss ( Physcomitrium patens) plants harboring a myosin XI temperature-sensitive allele. We found that loss of myosin XI function alters tip cell morphology, vacuolar homeostasis, and cell viability but not following F-actin depolymerization. Importantly, our conditional loss-of-function analysis shows that myosin XI focuses and directs vesicles at the tip of the cell, which induces formin-dependent F-actin polymerization, increasing F-actin's local concentration. Our findings support the role of myosin XI in vesicle focusing, possibly via clustering and F-actin organization, necessary for tip growth, and deepen our understanding of additional myosin XI functions. Abstract : Vesicle clustering by the molecular motor myosin XI enhances actin polymerization-dependent motility and polarized vesicle accumulation in tip-growing cells.